Accelerated CSharp 2010 - Nash, Trey (Apress, 2012)
Writing a book is a long and arduous process, during which I have received tons of great support, which I greatly appreciate, from friends and family. The process would have been much more difficult, and arguably much less fruitful, without their support. I would like to specifically call out the following individuals for their contribution to the first two editions of this work. I would like to thank (in no particular order) David Weller, Stephen Toub, Rex Jaeschke, Vladimir Levin, Jerry Maresca, Chris Pels, Christopher T. McNabb, Brad Wilson, Peter Partch, Paul Stubbs, Rufus Littlefield, Tomas Restrepo, John Lambert, Joan Murray, Sheri Cain, Jessica D’Amico, Karen Gettman, Jim Huddleston, Richard Dal Porto, Gary Cornell, Brad Abrams, Ellie Fountain, Nicole Abramowitz and the entire Apress crew, and finally, Shelley Nash, Michael Pulk, Shawn Wildermuth, Sofia Marchant, Jim Compton, Dominic Shakeshaft, Wes Dyer, Kelly Winquist, and Laura Cheu. During the development of the third edition, I would like to call out the following individuals for their help and support (again in no particular order): Jonathan Hassell, Mary Tobin, Damien Foggon, Maite Cervera.